Factors That Influence Knowledge Sharing in The Development of Farm Farming in Talang Keramat Urban Village of Banyuasin Ditrict - Junaidi, Yulian; Arbi, Muhammad; Silvian, Trissa; Berizki, Sindi (Journal of Economics and Business UBS, 2025)
The study on backyard farming in Talang Keramat Village analyzed knowledge sharing behavior and its influencing factors such as creativity, social support, appreciation, shared mentality, member diversity, team cohesiveness, education, extrinsic motivation, and social capital using a quantitative survey of 45 randomly selected respondents. Results show that all factors except extrinsic motivation significantly influence knowledge sharing behavior in the development of backyard farming. This behavior not only fosters social and environmental benefits, such as improved cooperation and a more organized, comfortable environment, but also supports the sustainability of backyard farming. The study implies that optimizing knowledge sharing through community-based and cross-sectoral approaches can further enhance the sustainability and impact of backyard farming. For future research, it is suggested to investigate the mechanisms of intrinsic motivation and digital platforms in facilitating knowledge sharing to strengthen community farming initiatives.